Agentive marking in Yongning Na (Mosuo) - Lidz, Liberty A. (2024)
Agentive marking in Yongning Na (Mosuo) appears with non-canonical constituent orders; with ellipsed patients; to indicate volitionality and agency; to mark contrastive focus/switch in actor; and acts as an utterance predicate with direct speech complements. Semantic extension has occurred from the contrastive focus usage of the agentive, which marks a constituent as salient, to an emphatic marker, which marks saliency on non-nominals. Although agentive marking often occurs in clauses with structural ambiguity, it often does not resolve this structural ambiguity. Structural ambiguity, however, rarely results in true ambiguity.